Cardiovascular risk assessment in people living with HIV compared to the general population. (10th December 2021) - Delabays, Benoît; Cavassini, Matthias; Damas, Jose; Beuret, Hadrien; Calmy, Alexandra; Hasse, Barbara; Bucher, Heiner C; Frischknecht, Manuel; Müller, Olivier; Méan, Marie; Vollenweider, Peter; Marques-Vidal, Pedro; et al.
Abstract: Aims: We prospectively assessed and compared the accuracy of cardiovascular risk scores in people living with HIV (PLWH) and individuals from the general population. Methods and results: The Systematic Coronary Risk Evaluation Score 2 (SCORE2), the Pooled Cohort Equations (PCE), and the HIV-specific Data Collection on Adverse events of Anti-HIV Drugs (D:A:D) score were calculated in participants free from atherosclerotic cardiovascular disease (ASCVD) between 2003 and 2009. In total, 6373 [mean age, 40.6 years (SD, 9.9)] PLWH from the Swiss HIV Cohort Study (SHCS) and 5403 [52.8 years (SD, 10.7)] individuals from the CoLaus|PsyCoLaus study were eligible for analysis. We tested discrimination and calibration, and the value of adding HIV-specific factors to scores using the net reclassification improvement (NRI). During mean follow-ups of 13.5 (SD, 4.1) in SHCS and 9.9 (SD, 2.3) years in CoLaus|PsyCoLaus study, 533 (8.4%) and 374 (6.9%) people developed an incident ASCVD, respectively. This translated into age-adjusted incidence rates of 12.9 and 7.5 per 1000 person-year, respectively. In SHCS, SCORE2, PCE, and D:A:D presented comparable discriminative capacities [area under the receiver operating characteristic curve of 0.745 (95% confidence interval, CI, 0.723–0.767), 0.757 (95% CI, 0.736–0.777), and 0.763 (95% CI, 0.743–0.783)]. Adding HIV-specific variables (CD4 nadir and abacavir exposure) to SCORE2 and PCE resulted in an NRI of −0.1% (95% CI, −1.24 to 1, P = 0.83) and of 2.7% (95% CI, 0.3–5.1, P = 0.03), respectively. Conclusions: PLWH present a two-fold higher rate of incident ASCVD compared to individuals from the general population. SCORE2 and PCE, which are clinically easier to use (reduced set of variables without adding HIV-specific factors), are valid to predict ASCVD in PLWH. Graphical Abstract: